Interleukin-1β and tumour necrosis factor-α levels in conjunctiva of diabetic patients with symptomatic moderate dry eye: case–control study. Issue 8 (3rd August 2016) - Zhang, Chen; Xi, Lei; Zhao, Shaozhen; Wei, Ruihua; Huang, Yue; Yang, Ruibo; Su, Long; Liu, Xun
Abstract : Objectives: To compare expression of interleukin (IL)-1β and tumour necrosis factor (TNF)-α in the conjunctiva of diabetic and non-diabetic patients with symptomatic moderate dry eye. Setting and participants: Nineteen diabetic patients with dry eye, 15 non-diabetic patients with dry eye and 14 diabetic patients without dry eye were recruited. The relative expression of IL-1β and TNF-α in conjunctival impression cytology (CIC) specimens was evaluated using immunofluorescent staining and in conjunctival biopsy specimens using immunohistochemical staining. Results: The diabetic dry eye group showed significantly higher grades of metaplasia than the non-diabetic dry eye and diabetic without dry eye groups (both p<0.05). There was no significant difference in the concentration of IL-1β and TNF-α in CIC specimens between the three groups (p=0.504 and p=0.310, respectively). The mean levels of IL-1β and TNF-α in conjunctival biopsy specimens from the diabetic dry eye group was significantly increased compared with the non-diabetic dry eye and diabetic without dry eye groups (p=0.002, p<0.001; p=0.001, p<0.001, respectively). Interestingly, IL-1β- and TNF-α-positive cells were mainly located in the basal layer of the conjunctival epithelium, and rarely seen in the apical conjunctival epithelium in the three groups. The levels of both IL-1β and TNF-α did not correlate with conjunctival squamous metaplasia grades. Conclusions: Levels of IL-1β and TNF-α in conjunctival biopsy specimens were increased in diabetic patients with dry eye, while levels of IL-1β and TNF-α in apical conjunctival epithelium were similar in the CIC specimens. These findings suggest that the inflammatory response is not limited to the surface of conjunctival epithelial cells, and is more serious in the basal layer of the epithelium, which may play an important role in the pathogenesis of dry eye in diabetic patients.